Experimental Study on Dynamic Compression Mechanics of Sandstone after Coupled Alkali-Chemical-Dynamic Interaction. (10th October 2022) - Ping, Qi; Wang, Chen; Gao, Qi; Shen, Kaifan; Wu, Yulin; Wang, Shuo; Li, Xiangyang
Abstract : For the purpose of analyzing the effect of the alkaline solutions on the mechanical property of sandstone impact compression, the sandstone specimens of coal mine roadway were corroded in NaOH solution with pH 7 (neutral pure water solution) and pH = 8, 9, 10, 11, and 12 for 28 d, followed by dynamic compression tests using a separated Hopkinson compression bar test device, and the microstructural changes of the specimens were measured by SEM electron microscope scanning equipment. The studies indicate that the degree of damage to the dynamic properties of a sandstone specimen is tightly correlated with the variation of the pH value of the corrosion solution. The corrosion deterioration effect of the strong alkaline solution is most obvious, followed by the weak alkaline solution, and the mechanical properties of the sandstone are relatively stable under a neutral solution. The dynamic compressive strength and dynamic modulus of elasticity of specimens decrease as a quadratic and cubic function, respectively, with the rising pH of the solution. The dynamic peak strain and average strain rate tend to increase with the increase in pH, and they are larger than those of the uncorroded specimens. As the pH of the solution rises, the impact damage of the sandstone specimens intensifies, and the average particle size of the fragments tends to decrease in a quadratic polynomial.